Greek Banking Expansion in South Eastern Europe and its Role in the Post-2009 Recession - Kokkinakis, Yiannis (International Journal of Economics and Financial Issues, 2016)
Capital investments by Greek banks in South Eastern Europe expanded rapidly during the period immediately before and after the introduction of the Euro. Through mergers and acquisitions, direct investments in a network of affiliated banks and subsidiary companies, as well as credit granted to Greek industrial capital invested in the region, by the mid-2000’s the Greek banking system had come to possess a substantial share of the entire South Eastern European banking sector. The commitment to support subsidiaries in the area has had negative consequences as regards the provision of credit and liquidity in the rapidly shrinking post-2009 Greek economy. The so-called Vienna initiative involved undertakings by major international financial bodies and the most important European institutions to maintain the exposure of western parent banks to emerging Europe. In conjunction with the Greek sovereign debt crisis, this increased the overall burden of the bailout loans, and hence EU and IMF involvement in Greece.This in turn contributed to the imposition of austerity measures that impaired an already fragile internal market. Keywords: Greek banks, Balkans, Vienna Initiative, financial crisis. jel Classifications: F36, G21, P34